Financial literacy and credit financing decisions among shallot farmers in Madura Island - Laili, Rosidatul; Wijayanti, Dian Eswin (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
Red onion commodities are a daily consumption necessity for society. Financial literacy refers to the ability and knowledge of individuals, such as farmers, to confidently make decisions in managing their finances. However, there is a lack of financial knowledge and management, leading to insufficient financial literacy among farmers. This study aims to determine the level of financial literacy and identify factors influencing financial literacy in relation to red onion farmers' financing decisions. The analysis methods used are the Financial Literacy Index (FLI) and binary logistic regression. Based on the research results in Bun Barat Village, Rubaru District, the financial literacy level of farmers is 70.79 percent, which falls into the moderate category. Financing decisions are influenced by education, age, income, land ownership, and the financial literacy index. Recommendations from this study include encouraging farmers to seek information about credit financing, advising financial institutions to provide more information and expand credit consultation services, and advising the government to offer guidance on effective financial management.